Evaluation of Different Types of Gallstones Extracted by Endoscopic Retrograde Cholangiopancreatography - Muhammad Ayub Naich, Sagheer Hussain, Adeel Qamar, Hina Zamir, Zia Ul Mustafa, Fatima Cheema (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To study frequency of various types of gall stones extracted from bile duct using ERCP Study design: This is a cross sectional study Study place and duration: Study was conducted in the department of Gastroenterology Sir Ganga Ram Hospital Lahore. Study was completed in six months duration from January 2022 to June 2022. Materials and methods: Diagnosed cases of bile duct stones were underwent ERCP and extracted stones were analyzed to determine their composition. Ages of the patients were 20-70 years. Cases of either gender irrespective of residential area were included in this study. Patients with ischemic heart disease, asthma, liver cirrhosis, malignancy, tuberculosis, chronic obstructive pulmonary disease, interstitial lung disease and pregnancy were excluded from the study. During ERCP gross findings of the stones were noted. Results: Total 140 cases were studied having bile duct stones including 55(39.3%) male and 85(60.7%) females. There were 80(57%) cases with the age ≤50 years and 60(42.9%) cases above 50 years. Mean age of the patients was 46 ± 4.72 years. 58(41.4%) cases were from rural area and 82(58.6%) from urban area. Diabetes, hypertension and obesity was found in 38(27%), 47(33.6%) and 49(35%) cases respectively. Cholesterol stones were found in 51(36.4%), mixed stones in 70(50%) and brown pigmented stones in 19(13.6%) cases. Conclusion: Mixed cholesterol gall stones were most commonly found followed by pure cholesterol and brown pigmented stones. Keywords: Gallstones, Bile duct stones, ERCP, Endocscopy, Cholesterol stones,